CRITICAL DISCOURSE ANALYSIS ON PAN POLITICAL BANNER CAMPAIGN USING FAIRCLOUGH THREE DIMENSIONAL MODEL - Aji Muhammad Akbar; Roby Salmon Agasi; Tito Yowata (Prasasti: Journal of Linguistics, 2019)
This study was conducted in order to explain of Partai Amanat Nasional (PAN) political banner campaign uniqueness within 2018-2019 campaign periods. This study focused on the linguistic feature which employed and discursive technique in the banner. The data was collected from internet and limited only to banner in West Java province. Fairclough 3D-model is used as framework in this study to see the relation of language and it implication in society. The findings disclosed that the whole banner discourse, including images, design, and language supports the construction of message in the banner. It was also PAN political banner campaign in West Java act as entertainment to the readers.